Green Chemistry and Process Intensification: Milestones on a Sustainable Development - Ghernaout, Djamel; Elboughdiri, Noureddine; Lajimi, Ramzi (International Journal of Chemistry and Materials Research, 2021)
As a philosophical support, green chemistry (GC) becomes at present well-combined into the scientific system to assist scientists and engineers consider how to decrease or remove waste and avert the employment and formation of hazardous substances in the design phase of chemicals. Such design attempts in turn affect the full life-cycle of the chemical, from getting the starting materials until the end-use product is recycled or disposed of. There is a considerable advance noted in such direction during the last three decades, this review focuses on GC research. As a comparatively fresh technique, revision in process intensification (PI) is fast and investigation could rapidly lead to outstanding outcomes. However, numerous features of PI could take more time to be fact. Much of the study stays in academic and industrial laboratories, even if large-scale implementations of micro-reactors are actuality. Fields of PI enterprise that have progressed quickly are the expansion of carbon capture techniques, an increasing interest in GC, and the beginning of momentous study into connecting solar energy to intensified methods like chemical reactions. Electric fields (e.g., microwaves and ultrasound) are observed in larger usages, and the application of electrokinetic forces at the micro- and nanoscale persist to fascinate. Huge investigations are working for the sake of ideas like the perfect reactor. PI remains a motif leading to attain a sustainable society. This work may be an orientation in the investigation of product development and design, production and application, in a constructive and stimulating way.